Occurrence, distribution and time-trend of arsenic in ground water of Jhikorgachha, Jessore, Bangladesh - Jakariya, Md.; Ahmed, Kazi Matin; Hasan, M. Abul; Nahar, Sultana; Rahman, Mahfuzar (BRAC Research and Evaluation Division (RED), 2019)
In order to assess the arsenic concentration change over time, water from a total of 246 tubewells Jhikargachha upazila of Jessore district were tested using atomic absorption spectrophotometer in two different periods of time. The main objective of the study was to develop a sustainable and affordable arsenic testing protocol for the arsenic affected communities of the country. While measuring groundwater arsenic concentration change over time, local hydrogeology and geostatistical relationship with arsenic were also analysed. It has been observed that movement of groundwater, according to elevation contour maps of dry and wet seasons of 1996, is from the central part of the study area towards the peripheral rivers. A relationship between arsenic distribution patterns and groundwater movement, though not obvious, could be established. Geostatistical analyses have been performed to investigate relationships between arsenic in groundwater with different well and aquifer parameters. A positive co-relation was observed between well depth vs. percentage of arsenic contaminated wells i.e. a general increasing trend of contaminated wells from 30 to 60m (~=0.81). This increasing trend changes at depth greater than 60m. The arsenic concentration results reveal that the highest number of tube well water showed change in concentration level in either case (i.e. increased or decreased). The highest increase was 91 J..lg/L and lowest decrease was 128.20 J..lg/L. This trend indicates that arsenic concentration in tubewell water can change in both directions but the tendency to reduce concentratio~ levels of arsenic in the analysed water was comparatively high. However, the findings of the study did not show any strong indication about changing the concentration level of arsenic in tubewell water.